Numerical investigation of pile foundation systems employing an enhanced embedded finite element - Granitzer, Andreas-Nizar; Felic, Haris; Leo, Johannes; Stastny, Alexander; Tschuchnigg, Franz (Frontiers in Built Environment, 2024)
The design of large-scale pile foundation systems is routinely assisted by finite element simulations. To a large extent, both the modeling and the computational effort of such analyses are governed by the adopted pile modeling technique. The traditional approach to this problem fully resolves the pile and soil domain employing solid elements, resulting in considerable meshing constraints and high simulation runtimes that may be regarded as unbearable for many practical purposes. As an attractive alternative to circumvent these obstacles, embedded FE models have become increasingly popular in solving this modeling task, mainly due to their flexible meshing procedure and significantly enhanced runtime efficiency. In a preceding contribution, the authors have proposed an extended formulation that provides a rigorous framework to capture soil-structure interaction effects at the physical soil-pile contacts. As a key feature, the implemented combined soil-pile coupling scheme explicitly accounts for endpoint interaction. However, validation studies have been constrained to single pile analyses to date. The present work expands this validation scope to large-scale boundary value problems involving multiple piles and investigates the model performance based on three different case studies. The results are compared to both, measurements and numerical benchmark solutions and provide exclusive insight into the numerical fidelity of the developed embedded FE model, with a view to increasing its potential for take-up in engineering practice.